Farmlend: a novel method or tackling agricultural waste in crop production - marketing & sales - Borresen, Victoria Torp (2023)
In the Field Lab, Building Companies Based on Science, students were given the opportunity to investigate a new scientific breakthrough. The students received a new patented live-metrics technology, with a mission to create a business plan, with a goal to establish a new company. The purpose of this business plan is to present how the company will tackle and face current challenges in the agricultural industry. In the making of the business plan, market research was conducted, followed by creating a solution, a new business model, a financial plan, and possible strategies to enter the market. The final business plan covers the essential elements to pitch the new company to partners and investors.